The Influence of Chief Risk Officer on the Effectiveness of Enterprise Risk Management: Evidence from Oman - Al-Farsi, Hamdan Abdul Hafidh (International Journal of Economics and Financial Issues, 2019)
This paper assesses the level of adoption and implementation of enterprise risk management (ERM) in Oman publicly listed companies and explores the influence of Chief Risk Officer (CRO) on ERM effectiveness. The data was collected using a structured questionnaire with a sample of 94 respondents including board of directors (BOD), chief executive officers (CEO), senior and junior management. The questionnaire was administered online using Survey Monkey for respondents to partake. Chi-square test, t-test, and Spearman rank correlation were used to validate the study hypotheses. The study found that there is a lack of awareness and knowledge of the procedures of enterprise risk management in most of the Omani publicly listed companies, and the level of adoption of ERM is at early stages. Moreover, the study confirmed that the Chief Risk Officer significantly influences and plays a key role in adopting and implementing ERM in the publicly listed companies in Oman. For Oman where there is a high dependency on oil, publicly listed companies are facing huge risk due to oil price volatility. Keywords: Chief risk officer, enterprise risk management, publicly listed companies, Oman JEL Classifications: G32, M14 DOI: https://doi.org/10.32479/ijefi.8932